Nutritional Project in School Setting: Analysis of Food Choices following Actions performed by Healthcare Workers - Federici, Giuseppina; Zulian, Nicole; Bino, Erica; Marcotrigiano, Vincenzo; Lovat, Alberto; Padoin, Angelo; Citiulo, Alessandro; Sava, Giovanni Andrea; Cinquetti, Sandro (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Schools continue to represent one of the main settings that guarantee health promotion interventions, as it has been widely demonstrated in numerous fields that diet and eating habits are shaped in the early stages of life and maintained into adulthood. Through the food education promotion project, “Healthy Snack”, implemented by the Prevention Department of the Local Health Authority ULSS 1 Dolomiti, the interventions carried out by healthcare workers have been evaluated over time to measure their effectiveness in terms of changes in eating habits considered incorrect, with a particular focus on snacks eaten at school.